Correlation Between Chlamydia trachomatis IgG and Pelvic Adherence Syndrome - Socolov, Demetra; Bleotu, Coralia; Miron, Nora; Socolov, Razvan; Boiculese, Lucian; Mares, Mihai; Natalia, Sorici; Veaceslav, Moshin; Botezatu, Anca; Anton, Gabriela (IntechOpen, 2012)
None